2003
DOI: 10.1242/jcs.00918
|View full text |Cite
|
Sign up to set email alerts
|

Long chain polyunsaturated fatty acids are required for efficient neurotransmission in C. elegans

Abstract: The complex lipid constituents of the eukaryotic plasma membrane are precisely controlled in a cell-type-specific manner, suggesting an important, but as yet, unknown cellular function. Neuronal membranes are enriched in long-chain polyunsaturated fatty acids (LC-PUFAs) and alterations in LC-PUFA metabolism cause debilitating neuronal pathologies. However, the physiological role of LC-PUFAs in neurons is unknown. We have characterized the neuronal phenotype of C. elegans mutants depleted of LC-PUFAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 41 publications
4
132
1
1
Order By: Relevance
“…C18 and C20 polyunsaturated fatty acids (PUFAs) have been shown to effect directed sperm movement towards the spermatheca and the formation of synaptic vesicles in neuronal tissues. [18,19] FAT-3 mutants lack the delta6 fatty acid desaturase and so cannot convert linoleic acid into C20 PUFAs because this desaturase activity is a prerequisite to subsequent elongase activity. [20] These mutants show a number of defects which are rescued by dietary supplementation of C20 and C18 PUFAs, including smaller brood size, alterations in the defecation cycle, and defects in chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…C18 and C20 polyunsaturated fatty acids (PUFAs) have been shown to effect directed sperm movement towards the spermatheca and the formation of synaptic vesicles in neuronal tissues. [18,19] FAT-3 mutants lack the delta6 fatty acid desaturase and so cannot convert linoleic acid into C20 PUFAs because this desaturase activity is a prerequisite to subsequent elongase activity. [20] These mutants show a number of defects which are rescued by dietary supplementation of C20 and C18 PUFAs, including smaller brood size, alterations in the defecation cycle, and defects in chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…This effect occurred already after short-term exposure of the worms to 10 µM 17,18-EEQ, whereas long-term feeding and much higher concentrations were required to achieve similar effects with AA or EPA. Also other authors found that high concentrations and a minimal time of about 24 h are required to restore the phenotype of fat-3 mutants by C20-PUFA supplementation [43][44][45][46][47][48]. Remarkably, the exogenously administered 17,18-EEQ increased the locomotion activity already under normoxic conditions and was effective not only with the mutant but to a lesser extent also with wild-type worms.…”
Section: Discussionmentioning
confidence: 96%
“…Within this process, 17,18-EEQ might also stimulate the release of neuropeptides that act as neurohormones onto body muscles. Providing a first link between C20-PUFA deficiency and neurotransmission, fat-3(lg8101) worms were shown to release abnormally low levels of neurotransmitters at cholinergic and serotonergic neuromuscular junctions and to be depleted of synaptic vesicles [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidences suggest that some membrane proteins may facilitate the transport of ALN and/or DHA through the hematoencephalic barrier. One of these transporters has been identified as a caveolin binding protein type or CD36 (Williard et al, 2001 ;Lesa et al, 2003). However, plasma levels of LCPUFA are poorly correlated with the dietary intake of the precursors (Kalant & Cianflone, 2004).…”
Section: Dha and Brain Metabolismmentioning
confidence: 99%